Pengaruh Pengetahuan Investasi, Return, dan Persepsi Risiko terhadap Minat Mahasiswa untuk Berinvestasi di Pasar Modal - Sari, Widya; Setiyawan, Susilo (Ma'soem University, 2024)
This research aims to determine the influence of investment knowledge, returns and risk perception on Ma'soem University students' interest in investing in the capital market. The method used in this research uses quantitative research methods. The population that will be the object is all Ma'soem University students. Meanwhile, the sample was selected using purposive sampling technique. The criteria required for sampling this research were Ma'soem University students who took part in seminars introducing sharia investment, and were willing to fill out the questionnaire provided at the end of the activity. So responses were obtained from 354 students, who then became the sample in this research. After validity test and reliability test, the data was transformed using the Method of Successive Interval. After all the data passed the classical assumption test, data analysis was carried out using multiple linear regression. The research results show that the investment knowledge variable does not have a significant effect on the investment interest variable. However, the return and risk perception variables each partially have a significant effect on the investment interest variable. Meanwhile, simultaneously, the variables are investment knowledge, return, and risk perception, has a significant effect on the student interest variable in investing in the capital market.